2012
DOI: 10.3109/00365521.2012.712999
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: symptom assessment using patient-reported outcomes in gastroesophageal reflux disease and dyspepsia

Abstract: There is considerable heterogeneity in the methodology used to develop PRO instruments for upper GI disease. Adherence to best practices in PRO development and validation may improve the quality and utility of these measures, leading to improved communication in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…In its guidance for industry, the US Food and Drug Administration recommends that questionnaires generally use short recall periods or ask patients to describe their current or recent state [5]. Asking patients to think back over a long period can reduce the accuracy of recall for all but the most memorable or stressful events [6], and may also make it more likely that the response is influenced by the patients' current state [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In its guidance for industry, the US Food and Drug Administration recommends that questionnaires generally use short recall periods or ask patients to describe their current or recent state [5]. Asking patients to think back over a long period can reduce the accuracy of recall for all but the most memorable or stressful events [6], and may also make it more likely that the response is influenced by the patients' current state [7].…”
Section: Introductionmentioning
confidence: 99%
“…PRO instruments for evaluating GERD symptoms are used to measure symptom intensity and frequency in clinical trial settings, and are valuable tools when assessing symptoms and deciding on disease management in primary care [6]. When asking patients to recall their GERD symptoms, the duration of the recall period used may be influenced by practical considerations.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, this finding has been noted in prior published research. 23 , 73 , 77 , 80 To illustrate, a recent review identified 65 questionnaires in use for the assessment of symptoms and outcome measures in GERD intervention trials alone. 73 …”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, there has been increasing integration of PROMs into cancer registries to collect outcomes such as overall quality of life, functional and psychosocial well-being, lifestyle behaviours and supportive care needs 45. Clinicians and patients may place different emphasis on symptom impacts and expectations from their treatment 46. The collection of PROMs is an important step in understanding patients’ experience of their symptoms and management and the impact of the disease and its treatment on their quality of life.…”
Section: Strengths and Limitationsmentioning
confidence: 99%